Morphoanatomical, physico-chemical standardisation and HPTLC analysis in the plant extract of Lepidagathis Scariosa (NEES) - Acanthaceae - S. SHARMILA,; R. NALLI,; M. SURUMBAYEE,; E.K. RAMYA, (International Journal of Pharma and Bio Sciences, 2018)
The objective of the study is to observe the macroscopic parameters and anatomical characterization of Lepidagathis scariosa (Nees) as protocol to be followed for botanical identification of the plant. Histochemical studies were made to localize different components, viz. alkaloids, phenolic compounds, flavonoids, lipids, starch and saponin in the tissues (Stem and Leaf) and to quantify flavonoid compound by HPTLC analysis with the use of standard marker compounds that is used in drug analysis. The study plant has a rich source of medicinal values. But no systematic studies is carried out for their anatomical and histochemical analysis, especially pharmacognostical studies on this plant remain unexplored. So the present attempt deals with the modest comprehensive investigation about macro morphological, micro anatomical characters and their pharmacopoeia standards perceived through physic-chemical constants. The pharmacognostic studies of Lepidagathis scariosa play a pivotal role in herbal technology as they lays down standardization parameters which will help and prevent adulterations.